2009
DOI: 10.1007/s11816-009-0102-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential antioxidation activities in two alfalfa cultivars under chilling stress

Abstract: To understand the adaptability of alfalfa (Medicago sativa L.) to chilling stress, we analyzed the antioxidative mechanism during seed germination. The germination rates of six alfalfa cultivars were studied comparatively at 10°C. Xinmu No. 1 and Northstar were selected as chilling stress-tolerant and stress-sensitive cultivars for further characterization. After chilling treatment, Xinmu No. 1 showed higher seedling growth than Northstar. Xinmu No. 1 exhibited low levels of hydrogen peroxide and lipid peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
1
12
0
2
Order By: Relevance
“…Each plant has its own anti-oxidative system where ROS-scavenging enzymes such as SOD (superoxide dismutase), CAT (catalase), APO (ascorbate peroxidase), POX (peroxidase) and GR (glutathione reductase) come into play along with non-enzymatic antioxidants such as glutathione (GSH), ascorbate (AsA) and carotenoids (Hasanuzzaman et al 2013). ROS quenching by anti-oxidative machinery is linked to stress tolerance, e.g., higher cold tolerance was observed in plants with enhanced activities of anti-oxidative enzymes in chickpea (Kumar et al 2011b) and alfalfa (Wang et al 2009). Soybean seedlings exposed to very low temperature (1°C) increased activities of anti-oxidative enzymes (Posmyk et al 2005).…”
Section: Temperature-induced Oxidative Stressmentioning
confidence: 99%
“…Each plant has its own anti-oxidative system where ROS-scavenging enzymes such as SOD (superoxide dismutase), CAT (catalase), APO (ascorbate peroxidase), POX (peroxidase) and GR (glutathione reductase) come into play along with non-enzymatic antioxidants such as glutathione (GSH), ascorbate (AsA) and carotenoids (Hasanuzzaman et al 2013). ROS quenching by anti-oxidative machinery is linked to stress tolerance, e.g., higher cold tolerance was observed in plants with enhanced activities of anti-oxidative enzymes in chickpea (Kumar et al 2011b) and alfalfa (Wang et al 2009). Soybean seedlings exposed to very low temperature (1°C) increased activities of anti-oxidative enzymes (Posmyk et al 2005).…”
Section: Temperature-induced Oxidative Stressmentioning
confidence: 99%
“…Thus, the chloroplast and mitochondria are the two most vulnerable to ROS. The cellular membranes and other macro-molecules, like proteins, nucleic acid, lipids, glycosides, etc., are more sensitive to cytosolic and organellespecific ROS (Wang et al 2009). Cellular impairment in terms of different metabolic events, which include chlorophyll attenuation, lipid peroxidation, protein carbonylation, oxidation of -SH groups of proteins and other organic moieties, reduction of enoic fatty acids, etc., are accelerated by these ROS and thus their cellular status or performance becomes retarded.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show elevation of SOD in chilling-stressed plants (Kuk et al 2003), while the others report decrease in its activity (Zhang et al 1995). It has been reported that genotypes expressing higher SOD activity possess superior cold tolerance (Huang and Guo 2005;Wang et al 2009). Our findings on CAT and APX activity are in agreement with observations on rice (Guo et al 2006) and alfalfa (Wang et al 2009), where cold-tolerant genotypes had greater activity of these enzymes.…”
Section: Discussionmentioning
confidence: 99%